MARKET PARTICIPATION BY SUBSISTENCE FARMERS: EVIDENCE FROM THE HIMALAYAS - D. B. Rahut; A. Ali; I. V. Castellanos; Pravakar Sahoo (Journal of Animal and Plant Sciences, 2015)
The importance of market participation for poverty reduction and the wellbeing of the subsistence farmers is proven beyond doubt. Increased market integration and commercialisation of traditional agriculture in the Himalayas is part of a development strategy towards growth and poverty reduction for more than 97% of households who are dependent on agricultural and allied activities for livelihood. This paper examines the roles of physical capital, human capital and the transaction cost in market participation in food crops, cash crops and livestock separately. The results show that the land size, gender of the household head, livestock assets, ethnicity, education, distances to market and location are important determinants of commercialisation. To estimate the impact of market participation on household income and poverty level, this paper uses propensity score matching approach. The results show a positive and significant relationship between the market participation and the household income, and a negative and significant relation between market participation and poverty levels, indicating that market participation can increase the well-being of rural subsistence farmers by increasing income levels and reducing poverty levels considerably.
Keywords: Market participation; small farmers; agricultural production; India; Himalaya